The Rat Hunting: A Street Parody - Ducca Durán, Isabel (2022)
In 2018, the denominated Combo Fiscal (Tax Combo) brought together a series of struggles and demonstrations, among which the so-called Marcha de los gatos (The Cats' March) stood out. This march was invisibilized by the media; however, it was massive and celebrated with great enthusiasm. The essay analyzes the presence of an official voice (Government) versus an unofficial voice (the people who go on strike). Furthermore, there are carnivalesque elements in the use of parody, a figure through which the official voice is derided with banners, texts and images. In addition, the presence of the grotesque is shown in the image of the rats to denigrate officialdom. These two elements, the rats and the four cats, represent the opposition between the official and unofficial voices (the visible and the invisible ones).